Modeling the effect of soil fertility management options on maize yield stability under variable climate in a sub-humid zone in Ghana - MacCarthy, Dilys S.; Adamtey, Noah; Freduah, Bright S.; Fosu-Mensah, Benedicta Y.; Ofosu-Budu, Godfred K.; Fliessbach, Andreas (Frontiers in Sustainable Food Systems, 2023)
Uncertainty in the yield of maize due to variability in weather is a major challenge to smallholder farmers in Sub Sahara Africa. This study explores the potential of combining locally available organic resources and inorganic fertilizer to increase grain yield and reduce variability in yields associated with variations in rainfall distribution. To assess the effectiveness of this practice, the Agricultural Production Systems sIMulator (APSIM) crop model was calibrated and evaluated using maize experiments on nutrient management options. The evaluated model was used to simulate maize growth and yield using multiple-year data (1984 -2018) under different planting windows for two growing seasons. The treatments were (i) control, (ii) inorganic fertilizer alone (INOFRecom), combining organic resources (empty fruit bunch of palm (EFB) and compost) with inorganic fertilizer (INOF) to make up equivalent nutrients in (ii)); (iii) EFB + INOF and (iv) Comp + INOF. Though all the soil amendments boosted grain output, the EFB+INOF treatment outperformed the other treatments in the major season with gains of between 161 and 211% and the most stable (least inter-annual variability of 27%) yield. Across the planting windows, the INOFRecom and EFB+INOF treatments achieved comparable yield increments in the minor season. Though grain yield variability was high during the minor rainy season, combining organic and inorganic fertilizers reduced inter-annual yield variability, thus, lowering uncertainty in yield due to variable inter-annual rainfall. These translated to higher water use efficiencies (WUE) based on cumulative rainfall from the EFB+INOF (6.91 -7.69 kg/ha/mm) treatment. Combining local organic resources with a reduced amount of inorganic fertilizer produced higher yields and better water use efficiency compared to using only inorganic fertilizer. Thus, such soil fertility management solutions might sustain resource use and boost maize grain yield in the study area, where strategies for sustainable crop nutrition remain a critical necessity. The improved nitrogen management regimes and water-use efficiency may result in fewer environmental hazards for vulnerable rainfed agricultural systems.